PENGARUH ASPEK KEJELASAN, KESESUAIAN, DUKUNGAN DAN BERDAMPAK TERHADAP TINDAKAN PEGAWAI KETIKA MENEMUKAN PELANGGARAN ETIKA: DARI MENGABAIKAN SAMPAI MENJADI WHISTLEBLOWER (STUDI KASUS DI 16 KANTOR PELAYANAN PAJAK) - , Eko Budiriyanto, Gugup Kismono, MBA., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research intended to know the influence of clarity, congruency, supportability, and sanctionability to the actions that would be taken by employees if they found ethic code breaking actions in their organizations. The probability of the actions that might be taken are: ignore it, make a direct confrontation (give a direct warning), send a report to superior, send a report through internal hotline, report to external party. The hipothesis were: clarity positively influence confrontations actions, send a report to superior, send a report through internal hotline, report to external party, and negatively influence to ignorance actions. Congruency of superior positively influence confrontations actions, send a report to superior, send a report through internal hotline, report to external party. Supportability positively influenced confrontations actions, send a report to superior, send a report through internal hotline, and negatively influence to ignorance actions. sanctionability positively influence confrontations actions, send a report to superior, send a report through internal hotline, and negatively influence report to external party and ignorance actions. The instrument items of this research were taken from the research conducted by Kaptein (2011) with modifications in several dependent variables, which were, made three breaking ethic cases with two cases was involving the superior. Subject of this research are the employees of 16 Kantor Pelayanan Pajak (KPP) spread in four regions. 20 employees were taken from each KPP using purposive sampling method. This research used regression analysis technique. As expected, clarity was positively related to confrontation, no relationship was found with reporting to superiors and inaction. Contrary to expectations, clarity was negatively related to calling internal hotline. Regarding the cultural dimension of congruency of local and senior management, a positive relationship was found with calling a hotline and external whistleblowing. Contrary to expectations, congruency of local and senior management was negatively related to confrontation and not related to reporting to management. The cultural dimension of supportability was not positively related to confrontation, reporting to management, not negatively related to inaction and contrary to expectations, negatively related to calling a hotline. Regarding the final hypothesis for sanctionability, positive relationships were indeed found for reporting to management, and calling a hotline, as well as a negative relationship with inaction. Contrary to expectations, sanctionability was positively related with external whistleblowing.